Meta-analysis of the effect of PGM on survival prognosis of tumor patients - Zheng, Zhewen; Bai, Jian; Shen, Shuangting; Zhu, Chunmei; Zhou, Yunfeng; Zhang, Xue (Frontiers in Oncology, 2022)
Objective: A systematic evaluation of the impact of phosphoglucose translocase PGM on the survival prognosis of tumor patients was conducted to understand its impact on tumors, in anticipation of improving the quality of survival and finding effective therapeutic targets for tumor patients. Methods: "PGM1"; "PGM2"; "PGM3"; "PGM4"; "PGM5" as Chinese keywords, "PGM1"; "PGM2"; "PGM3" PGM4"; "PGM5"; "PGM1 cancer"; "PGM2 cancer "; "PGM3 cancer"; "PGM4 cancer"; "PGM5 cancer"; The keywords "phosphoglucomutase" were searched in the databases of China Knowledge Network (CNKI), Wanfang, Wipu, PubMed, EMBASE, ScienceDirect, web of science and Cochrane Library. Relevant studies published from the database establishment cut-off to April 2022 were collected. Studies that met the inclusion criteria were extracted and evaluated for quality with reference to the Cochrane 5.1.0 systematic evaluation method, and the quality assessment was performed using Revman 5.3 software. Results: The final results of 9 articles and 10 studies with a total of 3806 patients were included, including 272 patients in the PGM1 group, 541 patients in the PGM2 group, 1775 patients in the PGM3 group, and 1585 patients in the PGM5 group. results of Meta-analysis: after counting the results of the 9 articles, the results showed that the difference was statistically significant with a P value <0.05 (HR=0.89, 95% CI 0.69 to 1.09, P=0.000). Looking for sources of heterogeneity, the remaining 8 papers were tested after removing the highly sensitive literature, and the results showed I²=26.5%, P<0.001, a statistically significant difference. the risk ratio (HR) for high expression of PGM1 and PGM2 and PGM5 was <1, while the risk ratio (HR) for high expression of PGM3 was >1. Conclusion: Although PGM1, PGM2, PGM3 and PGM5 are enzymes of the same family, their effects on tumors are different. high expression of PGM1, PGM2 and PGM5 can effectively prolong the overall survival of patients. In contrast, high expression of PGM3 reduced the overall survival of patients. The study of PGM family enzymes can provide help for subsequent tumor diagnosis, treatment and prognostic assessment.